APLICAÇÃO DE FUNGICIDAS EM DIFERENTES ESTÁDIOS FENOLÓGICOS DA CULTURA DO MILHO (Zea mays) NO CONTROLE DE DOENÇAS - Koguishi, Lincom (2011)
The objective of this study was to evaluate the effects of application timing of fungicides epoxiconazole + pyraclostrobin and azoxystrobin + cyproconazole in corn in the control of Phaeosphaeria leaf spot (Phaeosphaeria maydis), rust (Puccinia sorghi), Cercospora leaf spot (Cercospora zea-maydis), stain Diplodia (Diplodia macrospora) and stem rot. Three experiments were installed in a randomized block design with four replications in plots measuring 3.2 x 5.0 meters. In experiment 1, we applied the fungicide epoxiconazole + pyraclostrobin at a dose of 99.75 + 37.5 g ai ha-1, more mineral oil (Assist) at a dose of 500 mL pc ha-1 and Experiments 2 and 3 was applied fungicide azoxystrobin + cyproconazole at a dose of 70 gy + 28 ha-1, more paraffinic mineral oil (Nimbus) at a dose of 600 mL pc ha-1. In experiment 1, applications were made at the phenological stages V8, V16, V8 and V16, V12, V15, VT and R2, and evaluated the severity of Phaeosphaeria leaf spot and Cercospora leaf spot in at R3, R4 and R5 and rot stalk the stage R6. With the data of severity, we calculated the area under the disease progress curve to Phaeosphaeria leaf spot. The lowest AUDPC occurred in treatments with a V16 application, with two applications in V8 and V16, with controls from 74 to 80%. In Experiments 2 and 3, applications of fungicides were made in V8, V16, R2, V8 and V16, V8 and R2, and R2 V16, V8, V16 and R2. Was evaluated in experiment 2 to Cercospora leaf spot, Phaeosphaeria leaf spot and stem rot. In the control of Cercospora leaf spot were the best treatment applications in developmental stage V8, which coincided with the occurrence of disease in the crop. To Phaeosphaeria leaf spot, the lowest values were in AUDPC with two applications in V8 and V16, V16 and R2 and the three applications in V8, V16 and R2, with control ranging from 25 to 40%. In Experiment 3, we assessed the common rust, leaf spot Phaeosphaeria, stain and Diplodia stalk rot. To common rust treatments containing application in V8 were the most effective with the percentage of controls over 80%. In relation to Phaeosphaeria leaf spot, the best treatment for AUDPC was the three applications (V8, V17 and R2) with 27% control. The treatments did not control the stain of Diplodia. In three experiments, was also evaluated damaged kernels, weight of thousand seeds and productivity, there being only in experiment 2, significant difference in the number and developmental stage of application for the variables weight of thousand seeds and productivity, highlighting the three applications in V8, V16 (17), R2 and applications V16 (17), R2, V8, V17. Keywords: Phaeosphaeria maydis, Puccinia sorghi, Cercospora zea